2014
DOI: 10.1007/s12010-014-1208-4
|View full text |Cite
|
Sign up to set email alerts
|

Production and Properties of a Surface-Active Lipopeptide Produced by a New Marine Brevibacterium luteolum Strain

Abstract: Microbial-derived surfactants are molecules of great interest due to their environmentally friendly nature and low toxicity; however, their production cost is not competitive when compared to synthetics. Marine microorganisms are exposed to extremes of pressure, temperature, and salinity; hence, they can produce stable compounds under such conditions that are useful for industrial applications. A screening program to select marine bacteria able to produce biosurfactant using low-cost substrates (mineral oil, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…However, in that case the assay was performed under slightly different conditions, i.e. evaluation of the surface activity was performed at room temperature after incubating the biosurfactants at 4 °C for 24 h [ 41 ], while in our case the emulsions were let to form at 4 °C and using cold culture supernatant and solvents, resulting in stabilizing the formed emulsion. The fact that the produced bioemulsifiers were active at low temperature and high salt concentration is an optimal trait to be considered when application under seawater conditions are targeted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in that case the assay was performed under slightly different conditions, i.e. evaluation of the surface activity was performed at room temperature after incubating the biosurfactants at 4 °C for 24 h [ 41 ], while in our case the emulsions were let to form at 4 °C and using cold culture supernatant and solvents, resulting in stabilizing the formed emulsion. The fact that the produced bioemulsifiers were active at low temperature and high salt concentration is an optimal trait to be considered when application under seawater conditions are targeted.…”
Section: Resultsmentioning
confidence: 99%
“…These values are higher compared to those reported for chemical biosurfactants like Tween 80 (110 mg/l) [ 39 ] or Triton X-100 (150 mg/l) and to other marine bacteria such as Streptomyces sp. (36 mg/l) [ 49 ], Brevibacterium luteolum (40 mg/l) [ 41 ] and Halomonas sp. MB-30 (250 mg/l) [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kowalewski et al [137] found that a reduction in interfacial tension in an oil-water-bacteria system is an important feature in enhanced oil recovery, but it might be caused by bacteria themselves. It is worth mentioning, that the advantages of biosurfactants as environmental-friendly compounds with high surface-active properties allow also their use in soil-washing/flushing techniques, which are aimed at organic pollutants removal from contaminated soils [138], however without biodegradation processes [30,109,[139][140][141].…”
Section: Biosurfactants-enhanced Hydrocarbons Biodegradationmentioning
confidence: 99%
“…Marine Brevibacterium luteolum strain produced a lipopeptide that possesses bioremediation ability. Reduction of surface tension was detected to be the mechanism (Vilela et al 2014). Pseudomonas sp.…”
Section: Emerging Roles Beyond Medicine Bioremediationmentioning
confidence: 99%